In-situ current annealing of graphene-metal contacts - Harihara Ramamoorthy; Ratchanok Somphonsane (My University, 2018)
We study the effect of current-induced annealing on contact resistance between graphene and metal contacts, demonstrating that this technique may be used as an effective in-situ annealing procedure to improve the graphene-metal contact resistance which has long been an issue in the characterization of graphene-based devices. By studying as many as 30 devices with varying sample sizes and geometry, we are able to reduce the overall resistance systematically to around 400 Ω⋅μm, which is competitive with the best values obtained in the literature to treat this problem. We also demonstrate the effectiveness of current annealing in desorbing contaminants from the surface of the graphene layer, simultaneously shifting the charge-neutrality point to zero back-gate voltage, thus allowing the tuning of carrier density on both the electron and hole sides of the Dirac spectrum.
Keywords: Contact resistance; Graphene research and applications